Myocardial deformation in malignant mitral valve prolapse: A shifting paradigm to dynamic mitral valve–ventricular interactions - Pace, Nathalie; Sellal, Jean-Marc; Venner, Clement; Mandry, Damien; Marie, Pierre-Yves; Filippetti, Laura; Echivard, Mathieu; Fraix, Antoine; Girerd, Nicolas; Lamiral, Zohra; De Chillou, Christian; Sadoul, Nicolas; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives This study sought to assess the value of myocardial deformation using strain echocardiography in patients with mitral valve prolapse (MVP) and severe ventricular arrhythmia and to evaluate its impact on rhythmic risk stratification. Background MVP is a common valvular affection with an overly benign course. Unpredictably, selected patients will present severe ventricular arrhythmia. Methods Patients with MVP as the only cause of aborted SCD (MVP-aSCD: ventricular fibrillation and monomorphic and polymorphic ventricular tachycardia) with no other obvious reversible cause were identified. Nonconsecutive patients referred for the echocardiographic evaluation of MVP were enrolled as a control cohort and dichotomized according to the presence or absence of premature ventricular contractions (MVP-PVC or MVP-No PVC, respectively). All patients had a comprehensive strain assessment of mechanical dispersion (MD), postsystolic shortening, and postsystolic index (PSI). Results A total of 260 patients were enrolled (20 MVP-aSCD, 54 MVP-PVC, and 186 MVP-No PVC). Deformation pattern discrepancies were observed with a higher PSI value in MVP-aSCD than that in MVP-PVC (4.6 ± 2.0 vs. 2.9 ± 3.7, p = 0.014) and a higher MD value than that in MVP-No PVC (46.0 ± 13.0 vs. 36.4 ± 10.8, p = 0.002). In addition, PSI and MD increased the prediction of severe ventricular arrhythmia on top of classical risk factors in MVP. Net reclassification improvement was 61% (p = 0.008) for PSI and 71% (p = 0.001) for MD. Conclusions In MVP, myocardial deformation analysis with strain echocardiography identified specific contraction patterns with postsystolic shortening leading to increased values of PSI and MD, translating the importance of mitral valve–myocardial interactions in the arrhythmogenesis of severe ventricular arrhythmia. Strain echocardiography may provide important implications for rhythmic risk stratification in MVP.